Value Chain Analysis of Cassava (Manihot Esculeta) in Toba Samosir Regency, North Sumatera, Indonesia - Rut Tambun; Yosef Manik (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
The purpose of this study is to map out the value chain of cassava (Manihot esculeta) and to measure the extent to which the cassava commodity in Toba Samosir Regency, North Sumatera, Indonesia, could affect the economics of the relevant stakeholders. This study employed the value chain mapping analysis method to map out the existing supply chain models. Data and information have been collected using semi-structured interviews to selected sample that represent the stakeholders’ population along the cassava supply chain in Toba Samosir Regency. The stakeholders have been identified using snowball technique. SWOT analysis was employed to deploy policy strategy in improving the cassava benefit for the stakeholders. From the study, we obtain three models of supply chain of cassava, namely: (i) direct sale of cassava root to consumer model, (ii) cassava-based food model, and (iii) tapioca starch model. The margins of each node for each supply chain were estimated. The value chain map reveals that the value engineering of cassava commodities is not optimal, in which the final products produced by all models of supply chain are far below the potential possible value. We finally recommended some value-added improvement strategy; for example, diversifying the product of cassava derivative that is more valuable that is higher-grade tapioca flour and modification of cassava flour. Keywords: Value Chain Analysis, Cassava, North Sumatera.